Teaching Speaking to Senior High School Through Movie Discussion - Lutfiansyah Lutfiansyah (Scope : Journal of English Language Teaching, 2018)
The use of film as learning media can support teachers and students in learning speaking English process. Thus, it can develop the speaking skill, language content, and vocabulary mastery of the students. This can be used by the teachers as a media resource to help the students improve  their speaking skill. Film is a learning media for learners to access deeper about the introductory of new words, phrase, or even simple sentences. It also assists students to learn more about English expressions. It can be concluded that in order to help the students to practice their speaking skill, the teacher should pay more attention to material, media and activities in the class. The teacher is expected to be a good teacher in facilitating the learning process. Key words: teaching speaking, speaking skill, movie